Methanolic Extract of Ganoderma lucidum Induces Autophagy of AGS Human Gastric Tumor Cells - Filipa S. Reis (Molecules, 2015)
Ganoderma lucidum is one of the most widely studied mushroom species, particularly in what concerns its medicinal properties. Previous studies (including those from some of us) have shown some evidence that the methanolic extract of G. lucidum affects cellular autophagy. However, it was not known if it induces autophagy or decreases the autophagic flux. The treatment of a gastric adenocarcinoma cell line (AGS) with the mushroom extract increased the formation of autophagosomes (vacuoles typical from autophagy). Moreover, the cellular levels of LC3-II were also increased, and the cellular levels of p62 decreased, confirming that the extract affects cellular autophagy. Treating the cells with the extract together with lysossomal protease inhibitors, the cellular levels of LC3-II and p62 increased. The results obtained proved that, in AGS cells, the methanolic extract of G. lucidum causes an induction of autophagy, rather than a reduction in the autophagic flux. To our knowledge, this is the first study proving that statement.